2020
DOI: 10.1080/00224499.2019.1706072
|View full text |Cite
|
Sign up to set email alerts
|

Making and Communicating Decisions About Sexual Consent During Drug-Involved Sex: A Thematic Synthesis

Abstract: Sexual consent is a central component in the primary prevention of sexual violence. There is growing evidence of the impact that alcohol consumption has on sexual consent. However, there has been no review examining sexual consent in the context of other drug-taking. Published literature was sought using searches of: PsycINFO, PsycARTICLES, Scopus, Web of Science, CINAHL, MEDLINE and Open Dissertations. Unpublished literature, such as unpublished government or charity reports, were identified through Google se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…A recent review of the literature examined associations between sexual consent and substances other than alcohol. 26 Those findings suggested that people hold positive sex-related expectancies for cannabis use, including that it enhances intimacy, connectedness, and trust; the authors argued that this "heightened emotional connection" may increase people's willingness to engage in sexual activity. 26 In about 20% of the articles reviewed, drug use was described as improving clarity and decision-making abilities, which contrasts effects of alcohol consumption.…”
Section: Sexual Consent and Substance Usementioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of the literature examined associations between sexual consent and substances other than alcohol. 26 Those findings suggested that people hold positive sex-related expectancies for cannabis use, including that it enhances intimacy, connectedness, and trust; the authors argued that this "heightened emotional connection" may increase people's willingness to engage in sexual activity. 26 In about 20% of the articles reviewed, drug use was described as improving clarity and decision-making abilities, which contrasts effects of alcohol consumption.…”
Section: Sexual Consent and Substance Usementioning
confidence: 99%
“…26 Those findings suggested that people hold positive sex-related expectancies for cannabis use, including that it enhances intimacy, connectedness, and trust; the authors argued that this "heightened emotional connection" may increase people's willingness to engage in sexual activity. 26 In about 20% of the articles reviewed, drug use was described as improving clarity and decision-making abilities, which contrasts effects of alcohol consumption. Such increases in perceived clarity may empower people to believe they are capable of consenting to sex while using cannabis.…”
Section: Sexual Consent and Substance Usementioning
confidence: 99%
“…Substance use, especially of injection drugs, during sex increases the risk of HIV transmission [36,41,42]. Substance use during sex can affect an individual's ability to consent and assert their sexual preferences, resulting in low sexual relationship power [22]. This, in turn, is associated with an increase in high-risk sexual behaviors, such as condom-less sex [43].…”
Section: Sexual Relationship Powermentioning
confidence: 99%
“…Consequently, SMM who have endured forms of abuse were more likely to engage in risky sexual behaviors such as substance use [20], condom-less sex [21], and transactional sex [6]. Substance use can exacerbate low sexual relationship power since substance use can affect an individual's decision-making ability and also limit one's agency for sexual negotiation [22]. If substance dependency develops, the financial burden of sustaining dependency may increase financial need to engage in transactional sex [23].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, researchers have investigated associations between alcohol and/or other drug use and sexual violence, with some finding alcohol and/ or other drug consumption to be a risk factor for sexual assault (Anderson et al, 2017;Beynon et al, 2008;Slaughter, 2000). A common explanation for this is that alcohol and/or other drug use can impair an individual's cognitive and/or physical capabilities, thus leading to an increased vulnerability to sexual violence (Beynon et al, 2008;Smith et al, 2020).…”
Section: Introductionmentioning
confidence: 99%